Midwifery Care for Mrs. F at BPM Winda Sriwahyuni, S.Keb - Ismalillah Asmaini Nasution; Sri Rahmafriani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study addresses the persistent challenge of high maternal and infant mortality rates in Indonesia, particularly in regions with limited access to health services. The research aims to implement and evaluate comprehensive midwifery care for Mrs. F at BPM Winda Sriwahyuni, S.Keb Pematangsiantar, covering pregnancy, childbirth, postpartum, neonatal, and family planning. Employing a qualitative descriptive case study, the population comprised all pregnant women receiving care at the clinic from February to May 2025, with Mrs. F selected purposively as the sample. Data were collected using observation sheets, obstetric assessment forms, and medical records, and analyzed thematically through data reduction, presentation, and conclusion drawing. The results showed successful early detection of complications, effective health education, and care in accordance with national standards, maintaining maternal and infant health and supporting postpartum contraception. The study concludes that integrated, ongoing midwifery care is essential for reducing maternal and infant mortality, though broader studies and improved digital documentation are recommended for future research.